Esther's struggle for the nation of Israel in Esther 4:10-17 and its implications for the faith struggle of mothers today - pada, Marniati; Dethan, Femi; Tahu, Ricky Fransiskus; Kabu, Mirna; Josefina, Sari; Djawa, Maya (Lembaga Penelitian dan Pendidikan Mandala, 2025)
In the book of Esther 4:10-17 tells the story of Esther, a woman who was appointed queen of Persia, who dared to fight against Haman's evil plan to massacre the entire nation of Israel. This story aims to provide inspiration for today's mothers who face various challenges in fighting for their faith. They are invited not to be afraid to speak out for the truth, even though they face social and cultural challenges. Esther teaches the importance of strategy and courage in fighting for family values and faith. Trust in God, as shown by Esther, is the key to facing difficulties and achieving victory. Mothers can emulate Esther's courage and wisdom in defending their family and their faith. This research uses a descriptive qualitative approach, namely a research approach that aims to describe, understand and interpret social or cultural phenomena in depth by collecting existing data. Esther's struggle provides inspiration for mothers today to fight for their faith personally and within Christian families.